A comparison of an audiometric screening survey with an in-depth research questionnaire for hearing loss and hearing loss risk factors. (1st December 2016) - Mosites, Emily; Neitzel, Richard; Galusha, Deron; Trufan, Sally; Dixon-Ernst, Christine; Rabinowitz, Peter
Abstract: Objective : We assessed the reliability of a hearing risk factor screening survey used by hearing conservation programmes for noise-exposed workers. Design : We compared workers' answers from the screening survey to their answers to a confidential research questionnaire regarding hearing loss risk factors. We calculated kappa statistics to test the correlation between yes/no questions in the research questionnaire compared to answers from 1 and 5 years of screening surveys. Study sample : We compared the screening survey and research questionnaire answers of 274 aluminum plant workers. Results : Most of the questions in the in-company screening survey showed fair to moderate agreement with the research questionnaire (kappa range: −0.02, 0.57). Workers' answers to the screening survey had better correlation with the research questionnaire when we compared 5 years of screening answers. For nearly all questions, workers were more likely to respond affirmatively on the research questionnaire than the screening survey. Conclusions : Hearing conservation programmes should be aware that workers may underreport hearing loss risk factors and functional hearing status on an audiometric screening survey. Validating company screening tools could help provide more accurate information on hearing loss and risk factors.